PEMBELAJARAN BERBASIS DIGITAL DI JURUSAN KIMIA FMIPA UNNES (Jurnal Inovasi Pendidikan Kimia, 2019)
The rapid development of informatics and computer technology (ICT) has an impact on the world of education today. On the other hand, changes in the educational paradigm that previously embraced teacher-centered learning became student-centered learning, bringing very significant changes to the developedment of learning methods at this time. This study aims to improve student chemistry learning outcomes through digital based learning. Digital technology has developed widely, but has not been utilized in learning. Based on preliminary observations in the Department of Chemistry at UNNES, lecturers have difficulty in creating a learning atmosphere centered on student activities, so that lecturers are still be the main source of learning. These problems have implications for the quality of learning in the Department of Chemistry, which so far has not used digital learning. This study is a qualitative descriptive study by applying digital based learning through three stages, namely planning, implementation, and reflection (see). At the planning stage, create a digital learning scenario. In the implementation phase, apply the scenario in the class. During learning, observations are carried out by the teaching team. The reflection phase is conducted to review the learning process with a focus on student activities and class participation. The results of this study prove that digital based learning is one option that can meet the need to improve the quality of learning chemistry at the UNNES. The effect of digital-based learning strategies on student learning outcomes is 52.8%